Recommendations for the classification and nomenclature of the DNA-β satellites of begomoviruses - Briddon, R. W; Brown, J. K; Moriones, E; Stanley, J; Zerbini, M; Zhou, X; Fauquet, C. M (Archives of virology, 2008)
The symptom-modulating, single-stranded DNA satellites (known as DNA-β) associated with begomoviruses (family Geminiviridae) have proven to be widespread and important components of a large number of plant diseases across the Old World. Since they were first identified in 2000, over 260 full-length sequences (~1,360 nucleotides) have been deposited with databases, and this number increases daily. This has highlighted the need for a standardised, concise and unambiguous nomenclature for these components, as well as a meaningful and robust classification system. Pairwise comparisons of all available full-length DNA-β sequences indicate that the minimum numbers of pairs occur at a sequence identity of 78%, which we propose as the species demarcation threshold for a distinct DNA-β. This threshold value divides the presently known DNA-β sequences into 51 distinct satellite species. In addition, we propose a naming convention for the satellites that is based upon the system already in use for geminiviruses. This maintains, whenever possible, the association with the helper begomovirus, the disease symptoms and the host plant and provides a logical and consistent system for referring to already recognised and newly identified satellites.